Small airway disease: A new “phenotype” of obstructive airway disease - Shital Patil; Sham Toshniwal; Gajanan Gondhali (Annals of Medical Science and Research)
Small airways are usually defined as noncartilaginous airways with an internal diameter <2 mm. Robust data are available regarding small airway involvement in various obstructive airway diseases such as bronchial asthma and chronic obstructive pulmonary disease (COPD). Small airway disease (SAD) can present as a starting point of emphysema, and in few cases, SAD can present with emphysema. Thus, SAD in COPD is a different phenotype along with emphysema and chronic bronchitis. Although bronchial asthma is a disease of large and medium size airways, small airway involvement has been documented in asthma in late stage. Involvement of small airways in asthma is a clinical clue toward the role of inhaled antimuscarinic therapy in this phenotype. Spirometry is a simple and cost-effective but less reliable test to diagnose SAD in comparison to impulse oscillometry. Inhalation therapy with small particle size aerosol long-acting beta-agonist plus inhaled corticosteroids is recommended for treatment of SAD. Targeting small airways in asthma and COPD with ultrafine particle-size inhaled medicines with antimuscarinic drugs will have a successful treatment outcome.